Strategi Dinas Kesehatan Kabupaten Karawang Dalam Meningkatkan Mutu Pelayanan Vaksinasi Covid-19 - Rahdian, Farhan; Muslihat, Asep (Peneliti.net, 2023)
At the end of 2020, Indonesia, including Karawang Regency, is being tested in the form of health cases that need to be worried about. This is a concern for all the people of Karawang Regency due to the spread of the virus or COVID-19 disease. Several efforts have been made by the government to minimize the transmission of Covid-19, namely by administering the Covid-19 vaccine. The purpose of this study is to find out what strategies need to be implemented in improving the quality of Covid-19 vaccination services. The qualitative method used in this research is a descriptive approach. The results of this study are in the form of a strategy that need to be implemented in improving the quality of Covid-19 vaccination services such as accessibility, information and communication, public service innovation and medical staff training. Furthermore, the benefit of this research is that it can be a reference in improving the quality of Covid-19 vaccine services